Who resembles whom? Mimetic and coincidental look-alikes among tropical reef fishes. - D Ross Robertson (Public Library of Science (PLoS), 2013)
Studies of mimicry among tropical reef-fishes usually give little or no consideration to alternative explanations for behavioral associations between unrelated, look-alike species that benefit the supposed mimic. I propose and assess such an alternative explanation. With mimicry the mimic resembles its model, evolved to do so in response to selection by the mimicry target, and gains evolved benefits from that resemblance. In the alternative, the social-trap hypothesis, a coincidental resemblance of the model to the "mimic" inadvertently attracts the latter to it, and reinforcement of this social trapping by learned benefits leads to the "mimic" regularly associating with the model. I examine three well known cases of supposed aggressive mimicry among reef-fishes in relation to nine predictions from these hypotheses, and assess which hypothesis offers a better explanation for each. One case, involving precise and complex morphological and behavioral resemblance, is strongly consistent with mimicry, one is inconclusive, and one is more consistent with a social-trap based on coincidental, imprecise resemblance. Few cases of supposed interspecific mimicry among tropical reef fishes have been examined in depth, and many such associations may involve social traps arising from generalized, coincidental resemblance. Mimicry may be much less common among these fishes than is generally thought.